2021
DOI: 10.1210/clinem/dgab667
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Supplementation Improves Fasting Insulin Levels and HDL Cholesterol in Infertile Men

Abstract: Context Vitamin D has been linked with glucose and lipid metabolism. Men with impaired gonadal function have a higher risk of metabolic syndrome and mortality, and vitamin D status may be a reversible modulator. Objective Determine the effect of daily vitamin D and calcium supplementation for 150 days on glucose and lipid homeostasis in infertile men. Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
3
11
0
Order By: Relevance
“…5·2 pmol/l; P < 0·001) and higher serum ionised Ca (1·21 mmol/l v . 1·20 mmol/l; P = 0·010) compared with 138 placebo-treated men, as reported previously (10,12) . Moreover, there were no differences in weight, BMI or body fat mass (%) after the intervention between the two groups (12) .…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…5·2 pmol/l; P < 0·001) and higher serum ionised Ca (1·21 mmol/l v . 1·20 mmol/l; P = 0·010) compared with 138 placebo-treated men, as reported previously (10,12) . Moreover, there were no differences in weight, BMI or body fat mass (%) after the intervention between the two groups (12) .…”
Section: Resultssupporting
confidence: 85%
“…All participants were instructed not to consume vitamin D supplements > 400 mg daily during the trial. In this cohort, we have previously reported that BMI correlates with serum 25OHD and serum parathyroid hormone (PTH), and serum 25OHD was significantly higher and serum PTH was significantly lower in men with normal weight compared with men with overweight and obesity (12) .…”
Section: Methodsmentioning
confidence: 86%
“…Two double-blind, randomized, placebo-controlled trials showed that vitamin D supplementation, which increased the mean 25(OH)D concentrations to Ͼ40 ng/mL, could increase insulin secretion capacity and improve peripheral insulin sensitivity in patients with type 2 diabetes and individuals at high risk of diabetes (15,16). As shown in a doubleblinded, randomized, clinical trial, infertile men receiving vitamin D supplementation had lower fasting serum insulin concentrations, lower homeostasis model assessment of insulin resistance (HOMA-IR) index and higher high-density lipoprotein cholesterol (HDL-C) levels compared with the placebo group (17). A multicenter, single-blind, randomized clinical trial in patients with COVID-19 pneumonia revealed higher levels of anti-in-fl ammatory cytokine IL-10 and CD4 ϩ T cells in the patients allocated to supplementation with 10,000 IU/d vitamin D (with the mean 25(OH)D level of 29Ϯ 7 ng/ mL) than in those who received 2,000 IU/d vitamin D (with the mean 25(OH)D level of 19Ϯ 9 ng/mL).…”
Section: Discussionmentioning
confidence: 99%
“…Independently of other factors, vitamin D deficiency contributes to type 2 diabetes, insulin resistance, and metabolic syndrome [91,92]. Other than the genetic vulnerability, those confounding factors are not as proximal as vitamin D deficiency as a cause for COVID-19 and its complications [93].…”
Section: More Scientific Evidence Would Model Vitamin D's Contributio...mentioning
confidence: 99%